Hercules the hero - Carr, Jan (M. J.); Thompson, Del; Thompson, Dana (New York : Disney Press, 1997)
Hercules is transformed from bumbling mortal to ancient Greek hero as he takes on a host of evil villains.
At head of title: Disney's.
Keywords: Children's stories